A Rare Case of Interdigitating Dendritic Cell Sarcoma in the Nasal Cavity - Eun Jung Lee; Dong Woo Hyun; Hyung-Ju Cho; Jeung-Gweon Lee (Case Reports in Otolaryngology)
Interdigitating dendritic cell sarcoma (IDCS) is an extremely rare neoplasm that mainly arises from the lymphoid tissues of the immune system. Although this neoplasm typically occurs anywhere along the lymph nodes, it can also be found at extranodal sites, especially in the head and neck. We experienced a rare case of extranodal IDCS in the nasal cavity, a location that has not been previously reported. A 73-year-old woman presented with a polyp-like mass in the nasal cavity and underwent endoscopic sinus surgery. A histologic study confirmed the mass as IDCS by immunohistochemistry with S-100 antibody, and postoperative adjuvant radiotherapy was administered. Although the incidence is extremely rare, this case suggests that extranodal IDCS should be considered in the differential diagnosis of nasal cavity masses.